Tai Chi - Wollering, Loretta; Illustrated by Aiza, Hector (Australia Hinkler Books, 2013)
Tai chi is more than just an excellent form of exercise: it allows you to relax, heal and rejuvenate your mind and body. Anatomy of Fitness Tai Chi shows you how to increase your strength, coordination and flexibility while improving your mental focus.
Include Color Illustrations
Keywords: Tai chi for children -- Tai chi